2019
DOI: 10.1111/lam.13233
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological survey of sugar gliders (Petaurus breviceps) kept as pets in Italy

Abstract: The sugar glider (Petaurus breviceps) is a small, arboreal, nocturnal, gliding mammalian possum belonging to the marsupial infraclass. Exotic marsupials, including sugar gliders, are becoming popular companion pets and, consequently, the risk of potential infections that can be transmitted to humans should be investigated. Data on the role of the sugar glider as a possible carrier of pathogenic and zoonotic bacteria are scarce and fragmentary. Therefore, this study is aimed at evaluating the prevalence of pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Novel pathogenic agents could emerge from the large diversity of species present in EACs (Johnson et al, 2020). Recent studies detected a wide range of pathogenic bacteria present in popular exotic species (e.g., ball pythons, D'Cruze et al, 2020; sugar gliders, Varriale et al, 2019). For instance, a new nematode species Baylisascaris potosis closely related to Baylisascaris procyonis (responsible for severe and potentially fatal neurologic infections in humans) was described in wild‐caught kinkajous ( Potos flavus ) kept as pets in Japan (Tokiwa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Novel pathogenic agents could emerge from the large diversity of species present in EACs (Johnson et al, 2020). Recent studies detected a wide range of pathogenic bacteria present in popular exotic species (e.g., ball pythons, D'Cruze et al, 2020; sugar gliders, Varriale et al, 2019). For instance, a new nematode species Baylisascaris potosis closely related to Baylisascaris procyonis (responsible for severe and potentially fatal neurologic infections in humans) was described in wild‐caught kinkajous ( Potos flavus ) kept as pets in Japan (Tokiwa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance was detected within this panel with 59% resistant to gentamicin, 27% resistant to ceftazidime, 23% resistant to ciprofloxacin and 23% resistant to imipenem (Hirakawa et al, 2010). Rabbits (von Degerfeld et al, 2020), sugar gliders ( Petaurus breviceps ) (Varriale et al, 2019) and snakes (Goldstein et al, 1981) have also been identified with P. aeruginosa . In rabbits, it can cause pyometra; however, sugar gliders and snakes are thought to be carriers of P. aeruginosa .…”
Section: Assessmentmentioning
confidence: 99%